The Implementation of Project-Based Learning in Teaching Speaking in Indonesian EFL Classroom - Ahsan Muzri S; Abdullah Abdullah; La Sunra (ARRUS Journal of Social Sciences and Humanities, 2024)
The purpose of this study is to determine the effect of the implementation of project-based learning in Indonesian EFL classroom in order to enhance students’ speaking skill. Experimental design was adapted in this study. The participants of this study was the twelfth grade students of SMAN 2 SIDRAP in the academic year 2023/2024. Through a random sampling technique, the students of XII MIPA 6 was selected to be the research sample. The research instrument was speaking tests which conducted through pre-test and post-test. The result of the implementation of project-based learning in teaching speaking in Indonesian EFL classroom shows that the students’ speaking skill improved significantly. It was proved by result mean score of students’ pre-test and post-test which the students’ mean score in pre-test was 15.88 and the students’ mean score in post-test was 18.81. It indicates that the students’ mean score in post-test is higher than the students’ mean score in pre-test with the percentage of enhancement is 18.5%. It could be concluded that the implementation of project-based learning in teaching speaking in Indonesian EFL classroom can enhance students speaking skill.